CURRENT STATUS OF MEDICAL EQUIPMENT MANAGEMENT AT HO CHI MINH CITY ODONTO-STOMATOLOGY HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Background: Medical equipment (ME) plays a crucial role in healthcare delivery, particularly in specialized hospitals.Objective: To describe the current status of medical equipment management at Ho Chi Minh City Odonto-Stomatology Hospital in 2024.Materials and Methods: A descriptive cross-sectional study was conducted at Ho Chi Minh City Odonto-Stomatology Hospital in 2024. The study subjects included all 139 medical equipment items and 74 healthcare workers involved in the management, use, maintenance, and repair of medical equipment in the Departments of Surgery Anesthesiology and Intensive Care, Diagnostic Imaging, Laboratory, and General Outpatient Clinic.Results: The results show that the management, use, and maintenance of medical equipment are quite good, with 100% of equipment having complete management and maintenance records; the majority of healthcare workers rated the installation, use, and storage conditions as good and very good (≥89%). Although most equipment has been fully documented, about 8–9% of medical equipment still lacks complete information about the user, time, and condition after use. However, 91,9% of healthcare workers believe that emergency response capabilities are not adequate.Conclusion: Medical equipment management at Ho Chi Minh City Odonto-Stomatology Hospital has achieved certain positive outcomes; however, several shortcomings persist.
Keywords: medical equipment, medical equipment management, hospital.